Looking into EFL Students' Preferences in Turning On and Off Their Video Camera during Virtual Learning: What Does it Imply? - Kenti Sugiyati; Mercya Christ Sita Dewi; Widya Ratna Kusumaningrum (University of Darussalam Gontor, 2022)
Videoconferencing tools with their webcam features are among the platforms that support the implementation of an online learning system amid the Covid-19 pandemic. Thus, students' attitudes toward webcam use can carry out essential meanings on the teaching-learning process in distance learning. Through an explanatory case study, the study aimed to determine students' preferences toward webcam use; and the reasons behind their behaviour. The results indicated that Indonesian EFL students at an average level agreed to keep their webcams on during virtual classrooms. To this point, there are situations where they turn their webcams on and off during courses in a week. A number of reasons such as facing anxiety issues, having an internet connection problem, concerning their privacy; become the primary reasons why they turned the camera off. Findings also highlighted that even students had some difficulties using it, they tried to keep their cameras on during several courses, even it is not mandatory, in order to show respect and closeness to their lecturers and be more attentive in joining the online classes. Thus the study offers implications for educators to encourage—not as mandatory—their students to turn their webcam on during online classes. Emphasize that even if they are in an online learning classroom keeping their webcams on will demonstrates their socio-affective skills, namely showing respect, attentiveness, and closeness to their lecturers.